Penerapan Sistem Gadai Emas Dalam Meningkatkan Ekonomi Masyarakat Sibuhuan pada PT. Pegadaian Syariah UPS Sibuhuan - Lubis, Aminah; Junda Harahap; Siti Lidya Ningsi Lubis (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to determine the implementation of the gold pawn system in PT. UPS Sibuhuaan Sharia Pawnshop and to find out the application of the gold pawn system in improving the economy of the Sibuhuan community at PT. UPS Sibuhuan Sharia Pawnshop. This type of research is filed Research (field research). The data sources used by the researcher in this study are primary and secondary data. The data collection method is through interviews, observations and documentation and the data analysis method is data reduction, data presentation and conclusion drawn. The results of the study show that 1) the implementation of the gold pawn system in PT. UPS Sibuhuan Sharia Pawnshop is its application by starting the initial stage of gold pawn financing, the assessment stage is carried out by testing and researching the gold, the gold pawn financing disbursement stage, the Gold Pawn Financing Maturity stage, the gold pawn financing repayment stage. The application of the gold pawn system in an effort to improve the economy of the Sibuhuan community at PT.